Analisis Pengaruh Keputusan Investasi, Keputusan Pendanaan,Kebijakan Dividen Dan Tingkat Suku Bunga Terhadap NilaiPerusahaan (Studi Kasus Pada Perusahaan Manufaktur Yang Terdaftar Di Bei Tahun 2010-2014 - Fitriyani, Ulfiana, Drs. Atwal Arifin, M.Si., Akt., C.A (2016)
This study aimed to analyze the effect of the investment decision, financing decision, dividend policy an interest rate on the value of the manufacturing companies listed on the Indonesia Stock Exchange in 2010-2014.Populasi in this research is manufacturing companies listed in Indonesia Stock Exchange period 2010- 2014. The research method sample by purposive sampling according to criteria that have been determined. The data used to use secondary data to see the annual reports of companies listed on the Indonesia Stock Exchange. The number of samples collected as many as 649. The data were analyzed using classical assumption test. And to test the hypothesis using multiple linear regression analysis. The results of this study indicate that the investment decision and funding decisions can affect both the poor value of the manufacturing company. While the dividend decision and the interest rate does not significantly influence the value of the company.